PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII A DI SMPN 1 MANGARAN SITUBONDO - Rahmatillah Rahmatillah; Miftahus Surur (STKIP PGRI Situbondo, 2020)
This study aims to determine the learning outcomes of students who learn using a problem-based learning model, namely Problem Based Learning (PBL). This type of research is quantitative with the pre-experimental design using a one-shot case study. Determination of the sample using purposive sampling method, namely 23 students of class VIII A SMP Negeri 1 Mangaran. Collecting data using test instruments, namely pretest and posttest, which are then analyzed by t-test. The results of the analysis show that tcount> ttable or 4.060> 2.074, with a sig value of 0.001 <0.05, so it can be concluded that there is a significant difference in learning outcomes before (pretest) and after (posttest) using the Problem Based Learning (PBL) learning model. This result means that there is an effect of the Problem Based Learning (PBL) model on the learning outcomes of class VIII A students at SMP Negeri 1 Mangaran Situbondo.